(untitled) - Ellis, Rod. (New York, 2015)
This new, fully updated edition continues to provide an authoritative and highly readable introduction to key areas of theory and research in second language acquisition. Ellis presents a comprehensive overview of the different theories in this field and examines critical reactions to them. The book reflects recent trends in looking at cognitive and social aspects of second language acquisition, as well as examining the roles played by implicit and explicit instruction in language learning
Keywords: Second language acquisition.,Tiếp thu ngôn ngữ thứ hai